2016
DOI: 10.1111/tme.12368
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and reasons of donor deferral prior to blood donation process: a single centre experience

Abstract: This study reported a fairly similar pattern of donor deferrals as in other regional studies. Low haemoglobin levels and a history of hepatitis B infection were the most common factors for temporary and permanent donor deferrals, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 11 publications
5
8
1
8
Order By: Relevance
“…Khurram et al . reported a lower deferral rate for VNRBD, while Waheed and Zaheer reported that the deferral rate between VNRBD and replacement did not vary significantly. However, both studies were majorly dependent on replacement donors, whereas this study reports predominantly VNRBD.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Khurram et al . reported a lower deferral rate for VNRBD, while Waheed and Zaheer reported that the deferral rate between VNRBD and replacement did not vary significantly. However, both studies were majorly dependent on replacement donors, whereas this study reports predominantly VNRBD.…”
Section: Discussionsupporting
confidence: 88%
“…High deferral amongst females has also been reported by Waheed and Zaheer and Khurram et al . , also with a predominant male donor pool. In contrast, a study from western India by Agnihotri also reported males to have a gender comparative lower deferral rate.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations